Phase-field simulation of interactive mixed-mode fracture tests on cement mortar with full-field displacement boundary conditions. (September 2017) - Wu, T.; Carpiuc-Prisacari, A.; Poncelet, M.; De Lorenzis, L.
Highlights: Phase-field model simulating complicated fracture processes. Full-field displacements from digital image correlation for boundary conditions. Qualitative and quantitative comparisons between experiment and simulations. Abstract: Phase-field modeling is an elegant approach to simulate complicated fracture processes, including crack initiation, propagation, merging and branching in a unified framework without the need for ad-hoc criteria and on a fixed mesh. These capabilities can only be fully validated through the comparison with experiments featuring crack development histories and patterns of sufficient complexity. As opposed to conventional mixed-mode fracture tests with predefined loading, interactive tests with multiaxial loading which are controlled during the propagation of the cracks can create more complex and stable crack propagation patterns. Moreover, the development of measurement techniques such as digital image correlation (DIC) provides the possibility to quantitatively characterize the full-field kinematics during the tests. In this work, full-field displacements measured by DIC during interactive mixed-mode fracture tests on cement mortar specimens are adopted as boundary conditions for phase-field numerical simulations. Qualitative and quantitative comparisons are illustrated, demonstrating the capability of the phase-field approach to predict complex mixed-mode fracture phenomena in cement mortar and suggesting possible further developments.